E-privacy: Evaluating a new search cost in online environments - Dirk Annacker; Sarah Spiekermann; Martin Strobel (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
Electronic Commerce environments increasingly witness a conflict on the subject of e-privacy: While marketers want to maximize their customer knowledge and grasp the identity of their online users, consumers often want to stay anonymous and not reveal private information. The conflict suggests that private consumer information should be respected as a new search cost for consumers in EC environments. The current paper aims to grasp the phenomenon of this new search cost entitled as private consumer information cost (PCIC). The paper aims to evaluate PCIC by identifying its main drivers and their interrelation. An empirical study is presented which shows that three factors, perceived importance, legitimacy and difficulty of online requests made by marketers in a purchase context explain much of the variance of PCIC. Empirical data also reveals how different types of information requests drive PCIC. The types of information distinguished are product information, information on product usage as well as personal information. Results hint at the fact that consumers accept personal information requests to a greater extend than one would expect, but only as long as they improve product- or service choice. It is concluded that marketers incur considerable opportunity cost of information if they do not respect the nuances evident in PCIC creation and do not rely on them for the strategic design of their online communication.
urn:nbn:de:kobv:11-10050573
Keywords: 330